Inferences About Trends in Labor Force Satisfaction: A Causal-Correlational Analysis - Organ, Dennis W. (Academy of Management Journal, 1977)
Analysis of five simplified causal models of the time trend of labor force job satisfaction reveals a stable pattern of job attitudes for the entire post-war period. Underlying this stability are developments tending to increase satisfaction, but offset by a larger portion of the labor force in younger age groups, which historically tend to have lower satisfaction. Analysis suggests that the stability of labor force satisfaction from 1947 to 1976 probably masks a trend of rising satisfaction until the early 1960s, followed by some decline through the subsequent decade as a concomitant effect of changes in the age structure of the work force.